Underwater Sound Sources and Ambient Noise in Fowlers Bay, South Australia, during the Austral Winter - Ward, Rhianne; McCauley, Robert; Gavrilov, Alexander; Charlton, Claire (SPRINGER SINGAPORE PTE LTD, 2019)
© 2019, Australian Acoustical Society.